Quran Learning Innovation At Rumah Tahfidz Al-Quran (RTQ) Dinar - Irfan, Ahmad; Romdhoni, Rohmat; Setiady, Dicky (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
The current problem is when children are far from the Quran, therefore the role of Quran learning institutions is needed to nurture the future generation through innovative and relevant learning methods. This study aims to determine the existing learning programs in RTQ Dinar, their processes, and the factors that hinder and support learning. The research method used is qualitative ethnographic research, with descriptive analytical data presentation. Primary data was obtained through interviews with the foundation head and examiners from Ummi. The results of this study show that the learning program consists of various levels similar to formal schools, and there are also graduation exams. The learning process is conducted using the Ummi method. Supporting factors include the quality of teachers, teacher remuneration, and the relationship between the institution and the students' guardians. The inhibiting factors include student inconsistency, inconsistent timing, and teacher turnover.   Keywords: Innovation, Learning, Quran